خۆشگوزەرانی کۆمەڵایەتی- مێژووی گەشەسەندنی و شێوازەکانی - عبدالله, پ. د. ئاسۆ ئیبراهیم; ساڵح, م. سەرنج عەزیز (Sulaimani Journal for Humanities, 2023)
Social welfare is one of the components of the governing systems of welfare countries, in which social services are provided to citizens without ethnic, religious or gender discrimination, based solely on citizenship. The welfare situation changes from one state to another and depends on different factors such as citizens' demands, unemployment rates and the number of retirees. The sciences that interpret and study social welfare are many, such as economics, political economics, psychology, philosophy, sociology, and social work. Each of these sciences reads from their own scientific point of view for social welfare. Sometimes there is a kind of connection between two or more sciences. And because this is a new topic in the libraries of Universities in Kurdistan, Iraq, we considered it important to conduct this research as an attempt to examine a sociological reading of social welfare.